Yogiro Hama - A life in time and space - Kodama, T.; Padula, S. S. (Sociedade Brasileira Fisica, 2007)
In this article we write a biographical note about Yogiro Hama. It is quite an amazing life story, as you will read in the pages below. In the second part of this article we include many messages and letters sent by several of his friends and collaborators for the celebration of his 70th birthday.
Keywords: hadronic collisions; hydrodynamics; heavy ion physics